Rapid recovery of soil arthropod assemblages after exotic plantation tree removal from hydromorphic soils in a grassland‐timber production mosaic. Issue 6 (1st July 2019) - Eckert, Michelle; Gaigher, René; Pryke, James S.; Samways, Michael J.
Abstract : Many wetland systems are being lost or degraded by human activities such as plantation forestry. Therefore, efforts to restore these wetland systems are important for biodiversity recovery. We assess the recovery of arthropod assemblages that occupy hydromorphic grassland topsoil and leaf litter after the removal of exotic pine trees. We sampled arthropods in three biotopes (natural untransformed hydromorphic grasslands, restored hydromorphic grasslands, and commercial pine plantations) replicated across a large‐scale timber‐grassland mosaic in the KwaZulu‐Natal Midlands, South Africa. In the restored sites, overall species richness, as well as species richness of spiders, ants, and orthopterans, was significantly higher than in plantations, and was as high as in natural, untransformed sites. Additionally, overall assemblage structure along with spider, beetle, ant, and orthopteran assemblages showed no significant differences between restored and natural grasslands. Therefore, pine tree removal enables recovery of these arthropod taxa to levels similar to those in natural hydromorphic grassland. Recovery was rapid, with the assemblages in some restored sites resembling those in untransformed sites after only 6 years, indicating a high level of resilience and recovery in these systems. Contrary to expectations, time since pine removal had a negative effect on arthropod recovery. This was due to the strongly negative effect of alien invasive American bramble ( Rubus cuneifolius ), which was most common in older restored sites, causing deviation from their restoration trajectory. The potential for arthropod recovery in these hydromorphic grasslands is high, but successful restoration is dependent on ongoing appropriate grassland management, especially removal of bramble.